Implementation of Religious Literacy Activities in the Formation of Religious Character of Students of Miftahul Ulum Islamic Middle School - Sholihah, Ifrohatus; Fitriyah, Lailatul (Journal Analytica Islamica, 2025)
This study examines the implementation of religious literacy activities in the formation of students' religious character at Miftahul Ulum Islamic Middle School. This religious literacy program aims to develop students' religious character through routine activities such as reading Surah Al-Waqi'ah, Asmaul Husna, dhuha prayer, and dzuhur prayer in congregation. These activities are designed to help students understand and apply religious principles in their daily lives, while improving religious understanding and better worship habits. This study uses a qualitative approach with a field research method, involving interviews with the principal, Islamic Religious Education (PAI) teachers, and students, as well as analysis of related documents. The results of the study indicate that religious literacy activities play an important role in improving student discipline, strengthening their relationship with God, and developing their religious character. Supporting factors for the implementation of this program include student motivation, as well as collaboration between teachers, parents, and the community. Meanwhile, inhibiting factors include bad habits of students, less attentive parenting patterns, and the influence of the external environment. This study contributes to the development of more effective educational strategies in forming religious character through religious literacy in schools.